Post-anesthetic CPS and EQUUS-FAP scores in surgical and non-surgical equine patients: an observational study - Reed, Rachel Anne; Krikorian, Anna M.; Reynolds, Rose M.; Holmes, Brittany T.; Branning, Megan M.; Lemons, Margaret B.; Barletta, Michele; Quandt, Jane E.; Burns, Charlotte C.; Dantino, Stephanie C.; Sakai, Daniel M. (Frontiers in Pain Research, 2023)
Background Equine pain scoring may be affected by the residual effect of anesthetic drugs. Objectives To compare pain scores in the hours immediately following anesthetic recovery to baseline pre-anesthetic scores in equine patients undergoing surgical and non-surgical procedures. Study design Clinical observational study. Methods Fifty adult horses undergoing anesthesia for surgical or non-surgical procedures were enrolled. Horses underwent pain scoring using the Composite Pain Score (CPS) and Equine Utrecht University Scale for Facial Assessment of Pain (EQUUS-FAP) prior to anesthesia (T0) and following anesthetic recovery to standing, every hour for 5 h (T1-T5). Data were analyzed using a generalized linear mixed effects model. A post-hoc Dunnett's test for multiple comparisons was performed for variables where an effect was detected. Results Mean (95% confidence interval) CPS scores for T0-T5 were 1.6 (1.2–2.0), 6.8 (6.0–7.6), 5.1 (4.3–5.9), 4.3 (3.4–5.2), 3.7 (2.8–4.6), and 2.8 (2.0–3.6) and EQUUS-FAP scores were 0.6 (0.3–0.9), 3.0 (2.5–3.5), 1.9 (1.6–2.2), 1.1 (0.8–1.4), 0.6 (0.4–0.8), and 0.7 (0.4–1.0), respectively. For the CPS, scores greater than 5, and for the EQUUS-FAP scores greater than 3, are consistent with minor pain. There was no effect of type of procedure (surgical vs non-surgical) on CPS or EQUUS-FAP scores. There was an effect of time with CPS scores significantly greater than baseline at T1-T5 and EQUUS-FAP scores significantly greater than baseline at T1 and T2. Main limitations Discomfort caused by hoisting was not quantified and it was difficult to ascertain if this affected the results. Conclusions Post-anesthetic pain scores may be influenced by the residual effect of anesthetic agents for as long as 5 h and 2 h for the CPS and EQUUS-FAP, respectively.